How are media discourses impacted by the use of different languages? A comparison of the French, English, and Arabic discourses on France 24 regarding freedom of expression and Islam - Moalla, Sonja; Cozma, Ana-Maria (France, 2025)
This article aims to investigate three media languages on France24 based on discussions regarding freedom of expression and Islam. The corpus was selected from France24 YouTube channels produced between 16.10.2020 to 16.12.2020; in the two months following the murder of Samuel Paty. These discussions are examined using corpus-based discourse analysis focusing on the lexical and syntactical structures. Collocation and frequency analyses are also carried out to examine the differences and similarities in the use of English, Arabic and French languages on France24. The findings reveal that the discourses on France24 are affected by media language. The differences in the three media languages include the way freedom of expression is referred to, the collocations used, and the level of differentiations when referring to “THEM” (versus “US”).